SENTRA KERAJINAN KERAMIK DENGAN PENERAPAN ARSITEKTUR EKSPRESIONISME DI JALAN IR. HAJI JUANDA REMPOA, TANGERANG SELATAN - Isra Wahyudin; Mieke Choandi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Jalan Ir. Haji Juanda is the main access that connects the city of South Tangerang with South Jakarta, resulting in high density and potential opportunities for business people. Seeing business opportunities and interest in fine art objects, in 1974 a fine art shop appeared called an "art shop". The development of art shops gives birth to positive identities and impacts socially, economically and culturally for society. Over time, the identity of the area began to fade and there was degradation in the art shop, it seemed that some shops still survived, others labeled "temporarily closed shops". The physical condition of the art shop building was damaged, unkempt due to inactivity of function so that a negative image arose in the area. It is hoped that the center for the craft of ceramic art as an attractor is a form of micro-scale intervention in urban structures, seeing the growing trend of ceramic workshops and the demand for the manufacturing process, the application of the architectural method of expressionism looks at the expressions formed from the process of making ceramics, which are poured through the façade elements that become the points of the face of the building, the inner space and the mass composition in the form of a circle base that moves following the direction of the rotary technique. The design aims to increase the identity and enthusiastic drive of the development of art shops, both for the local community, especially business people, art actors and tourists Keywords: Businessman; Fine arts crafts; Regional identity Abstrak Jalan Ir. Haji Juanda merupakan akses utama yang menghubungkan kota Tangerang Selatan dengan Jakarta Selatan, sehingga terjadi kepadatan tinggi dan potensial peluang bagi pebisnis. Melihat peluang bisnis dan ketertarikan benda seni rupa, tahun 1974 muncullah toko karya seni rupa dengan sebutan “art shop”. Berkembangnya art shop melahirkan identitas dan dampak positif secara sosial, ekonomi dan budaya bagi masyarakat. Seiring berjalan waktu, identitas kawasan mulai pudar dan terjadi degradasi pada art shop, nampak ada toko masih bertahan, yang lainnya berlabelkan “toko tutup sementara”. Kondisi fisik bangunan art shop mengalami kerusakan, tidak terawat karena tidak aktifnya fungsi sehingga timbul citra negatif pada kawasan. Diharapkan Sentra kerajinan seni rupa keramik sebagai atraktor wujud dari intervensi skala mikro pada struktur perkotaan, melihat tren workshop keramik yang sedang berkembang dan diminati akan proses pembuatannya, penerapan metode arsitektur ekspresionisme melihat dari ekspresi yang terbentuk dari proses pembuatan keramik, yang dituangkan melalui elemen fasad yang menjadi poin wajah bangunan, ruang dalam dan gubahan massa yang berbentuk dasar lingkaran yang bergerak mengikuti arah teknik putar. Perancangan bertujuan meningkatkan identitas dan penggerak antusias berkembangnya art shop, baik bagi masyarakat lokal khususnya pebisnis, pelaku seni hingga wisatawan.